First Real-World Insights into Belimumab Use and Outcomes in Routine Clinical Care of Systemic Lupus Erythematosus in Germany: Results from the OBSErve Germany Study. Issue 2 (December 2016) - Schwarting, Andreas; Schroeder, Johann; Alexander, Tobias; Schmalzing, Marc; Fiehn, Christoph; Specker, Christof; Perna, Alessandra; Cholmakow-Bodechtel, Constanze; Koscielny, Volker; Carnarius, Heike
Abstract OBSErve Germany was the first observational study of belimumab as add-on treatment for systemic lupus erythematosus (SLE) in routine clinical care in Germany, retrospectively collecting data from 102 SLE patients, 6 months before and after belimumab initiation. Most patients had moderate or severe SLE and several SLE manifestations. After 6 months of belimumab treatment, 78% of patients showed an improvement in overall disease activity of at least 20% in their physician's judgment and for 42% of patients the improvement was at least 50%. Similar results were observed for the most common manifestations: arthritis, fatigue, rash, alopecia, increased anti-dsDNA antibody levels, and low complement. The SLE Disease Activity Index (SLEDAI/SELENA-SLEDAI) decreased from 10.6 to 5.6 (n = 65), with other indices also showing improvement. A notable dose reduction was seen for concomitant oral corticosteroids, from 13.7 to 7.6 mg/day overall (n = 91), and from 17.5 to 8.6 mg/day in patients with a high corticosteroid dose at belimumab initiation (≥7.5 mg;n = 63). Six patients discontinued belimumab therapy within 6 months. Overall, belimumab showed promising results for SLE patients in real-world settings. After 6 months of belimumab treatment, disease activity and corticosteroid use were reduced. The discontinuation rate was low and belimumab appeared to be well tolerated. Funding GlaxoSmithKline UK.